Kajian Biografi: Darwis Loyang Sebagai Tokoh Tari Melayu Sumatera Barat - Triatmi, Shelfi Velfekti; Nurmalena; Syofia, Ninon; Basra, Sri Meiweni (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to examine the biography of Darwis Loyang as an important figure in the development of Malay dance in West Sumatra. The research method used is qualitative with a descriptive-analytical approach, which involves describing data as found in the field and then analyzing it in depth. In this study, the researcher utilizes theories or opinions including Sukirno's views on biography, Supriadi's views on creativity, and Soerjano Soekanto's views on contribution. The results of this study focus on the life, works, and contributions of Darwis Loyang in introducing and developing Malay dance, particularly in the city of Padang. Darwis Loyang is a central figure who brought the cultural influence of Deli Malay from Medan to West Sumatra since the 1950s. He is actively involved as a creator, trainer, and preserver of Malay dance, and founded the Alang Babega Dance Studio, which serves as a platform for nurturing the younger generation.